(untitled) (Journal of Environmental Bioremediation and Toxicology, 2021)
In this review, various aspects of acetylcholinesterase (AChE) are reviewed. Acetylcholinesterase (AChE, EC3.1.1.7) is an important neurotransmitter because it hydrolyses the neurotransmitter acetylcholine (ACh), it is also the target site of organophosphorus and carbamate insecticides. The discovery of the first neurotransmitter ACh was soon followed by the discovery of its hydrolysing enzyme, AChE. The role of AChE in terminating AChE-mediated neurotransmission made it the focus of intense research for much of the past century. The role of butyrylcholinesterase (BChE) is not known but it is assumed to participate in the growth and development and to scavenge the cholinergic toxins, it is also reported to have an auxiliary role in synaptic transmission. Acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) are the major groups of cholinesterase differentiated by their substrate preferences. Substrate binding specificity and catalytic efficiency are tangled in enzyme catalysis. The fact that an enzyme may exist in more than one molecular form has been accepted for a number of years.